Irradiation studies on a reactor pressure vessel steel using Fe+ ion. (11th September 2019) - Kedharnath, A; Sarkar, Apu; Kapoor, Rajeev; Balaji, S; David, C; Dutta, Dhanadeep; Sharma, S K; Reddy, G Bharat; Sunil, Saurav; Chatterjee, Arnomitra; Kumar, Harish; Thool, Khushahal
Abstract: Reactor pressure vessel steel samples were irradiated to three different doses 10, 25 and 50 displacements per atom (dpa) at 300 °C (reactor operating temperature) with 1.76 MeV Fe + ion and at the dose rate of ∼4.4 × 10 −3 dpa s −1 . Samples were examined by Electron Backscatter Diffraction (EBSD), Grazing Incidence x-ray Diffraction (GIXRD), depth dependent Doppler Broadening Spectroscopy (DBS) and nanoindentation before and after irradiation. EBSD showed an increase in local misorientation values suggesting an increase in geometrically necessary dislocation density. GIXRD showed an increase in overall dislocation density after irradiation. DBS results suggested a non-uniform vacancy-depth distribution with the highest damage at a depth (∼500 nm) which was consistent with the values from the Stopping and Range of Ions in Matter (SRIM) calculations. The mechanical response after irradiation was measured using nanoindentation. The nanohardness of the irradiated samples was higher than that of the unirradiated one and increased with the increase in dpa. GIXRD result showed that the dislocation density of 50 dpa irradiated sample was almost twice that of the unirradiated sample.